Economy and Environmental Ethics in the Qur’an: A Thematic Interpretation Study on Sustainable Development - Desy Arum Sunarta; Achmad Abubakar; Muhammad Irham (Jurnal Studi Ilmu Sosial dan Politik, 2026)
Purpose: The study of the synergy of economics and environmental ethics in the Qur'an is becoming increasingly relevant in the context of efforts to find alternative solutions to conventional development models that often ignore environmental aspects and social justice. Methodology: The research approach method uses a comprehensive literature study that aims to collect and analyze in depth various literature related to the synergy of economics and environmental ethics. Results: The Qur'an guides humans to manage the earth with full responsibility. Sustainable development in Islam is not only about economic growth, but also moral, social, and ecological preservation. The goal of development according to Islam is not just economic growth, but fair and equitable welfare, and the preservation of Allah's creation. Islam encourages a circular economy and a sustainable lifestyle. Conclucions: Islamic teachings, as interpreted thematically from the Qur’an, provide a comprehensive ethical framework that supports sustainable development. This framework integrates environmental conservation with equitable economic growth, emphasizing responsible resource management and distributive justice as essential components of a just and sustainable society. Limitations: This study is limited to textual and conceptual analysis without empirical validation or field-based data. Future research may consider integrating empirical methods to assess practical applications of Qur’anic environmental ethics in modern economic systems. Contributions: The study contributes to the growing field of Islamic environmental ethics by offering a Qur’anic perspective on sustainability and proposing an alternative development paradigm rooted in Islamic theology.